An assay to measure levels of factor Xa inhibitors in blood and plasma. (10th May 2019) - Kim, Paul Y.; Di Giuseppantonio, Luca R.; Wu, Chengliang; Douketis, James D.; Gross, Peter L.
Abstract: Essentials Direct oral anticoagulants (DOAC) are used for stroke and venous thromboembolism prevention. We report a new assay that measures anti‐factor Xa DOAC levels in plasma and whole blood. Rivaroxaban and apixaban can be accurately quantified below trough levels. The ease and accuracy of the assay demonstrate its potential for point‐of‐care applications. Background: Rivaroxaban and apixaban are the most commonly used anti‐factor (F) Xa direct oral anticoagulants (DOAC), with indications for prevention of stroke in nonvalvular atrial fibrillation as well as treatment and prevention of venous thromboembolism. However, lacking is accessibility to a detection method that is able to quantify low levels of anti‐FXa DOACs. Objective: We report a new assay that measures anti‐FXa DOAC levels in plasma and whole blood. Methods: This is achieved by the use of a prothrombin derivative that is labeled with a fluorescent probe (Flu‐II), which then acts as the macromolecular substrate to measure residual FXa activity. The Flu‐II cleavage is then initiated by the addition of a solution containing FXa, FVa, and phospholipid vesicles composed of 75% PC and 25% PS (PCPS) vesicles with calcium, in the presence of hirudin to prevent feedback activity by the native thrombin generated. The Flu‐II cleavage is monitored by fluorescence in real time where the initial rate of fluorescence change is inversely proportional to DOAC levels. Results: In plasma systems, the assay demonstrates dose‐response between 0 and 5 nmol/L rivaroxaban and between 0 and 10 nmol/L apixaban. Corn trypsin inhibitor did not affect this assay. With individual plasma samples, the assay showed excellent consistency and reproducibility. From 2 μL of whole blood, the assay showed dose‐response between 0 and 2 nmol/L of DOACs in the final mixture of 100 μL, thus representing up to 100 nmol/L in circulating blood. Conclusion: The assay is ideal for rapidly and accurately measuring DOAC levels in plasma and blood, demonstrating its potential for point‐of‐care applications.